PHYSICAL EVIDENCE, RELIABILITY, RESPONSIVENESS, ASSURANCE AND EMPATHY OF SERVICE QUALITY ON INPATIENT PATIENT SATISFACTION: STUDY A REGIONAL GENERAL HOSPITALS - Yuyun Yunningsih (PT. Berkah Digital Teknologi, 2022)
Purpose: the study is to examine the relationship between various factors (physical evidence, reliability, responsiveness, assurance, and empathy) and patient satisfaction in a hospital setting. Specifically, it aims to determine the impact of these factors on patient satisfaction at Indramayu Hospital and to provide insight for hospital managers and administrators on how to improve patient satisfaction. Research Methodology: This study uses a quantitative type of research using a cross-sectional design or research design. The population in this study were all patients who came and used health services at the Indramayu Hospital, based on the latest report the number of patient visits in May 2021 was 2199 patients. The sampling technique used in this study is a non-probability sampling technique with the type of accidental sampling. Results: a study found that good physical evidence positively impacts patient satisfaction at Indramayu Hospital. Reliability, responsiveness, and empathy were found to have no significant effect on patient satisfaction, while assurance was found to have a positive significant effect on patient satisfaction. However, when all five factors (physical evidence, reliability, responsiveness, assurance, and empathy) were considered together, they had a positive and significant effect on patient satisfaction. These results suggest that a combination of good physical evidence, reliability, responsiveness, assurance, and empathy can positively impact inpatient satisfaction at Indramayu Hospital. Limitations: This study was only tested in one local government hospital, Contribution: This study can be useful in the area of healthcare management and patient satisfaction, specifically in hospitals. It can provide insight into how various factors such as physical evidence, reliability, responsiveness, assurance, and empathy can impact patient satisfaction. This information can be used by hospital administrators and managers to develop strategies for improving patient satisfaction at their facility. Additionally, it can be useful for researchers in the field of healthcare management and patient satisfaction, as it provides empirical data on how these factors can affect patient satisfaction. Additionally, this study can be useful for healthcare providers, as it can help them understand how to provide better care and service to their patients, which in turn can contribute to patient satisfaction.